Partnering to Scale Biofortified Crops in Uganda - International Potato Center (2018)
Under the USAID funded activity, “Meals for Nutrition: Biofortified Solutions”, a total of 82,800 farmers have been reached with orange sweetpotato vines and 176,079 farmers with high iron beans in 25 districts, between August 2017 and August 2018. This has been achieved through partnerships with five NGOs, six seed companies and 32 multipliers. Farmers access seed through seed loans and payback mechanisms and seed/vine sales by seed producers. Over 50 schools now purchase OFSP and iron beans from farmers for school feeding both at primary and secondary school level (Fig. 1). In addition, in partnership with Ministry of Agriculture, the National Biofortification Technical Working Group was constituted to lobby for biofortification in government.